CHEMICAL COMPOSITION, in situ AND in vitro DEGRADATION OF Kochia scoparia IN RELATION TO DATE OF SOWING AND AGE OF CUT - Jose Romero-Bernal (Tropical and Subtropical Agroecosystems, 2011)
The Kochia scoparia is an alternative source of medium-quality protein for food in ruminants, for this, it is important to know its chemical composition and its degradation and fermentation in the rumen, as this can vary depending on the date of establishment and cutting age. In the present study evaluated the chemical composition. The degradation assessment was performed using the technique of in vitro gas production and ruminal in sacco degradation. The Kochia scoparia cultured on three dates (D) of sowing(D1, 07/12/2001; D2, 06/01/2002; and D3, 05/02/2002) and the cut was made at two different ages (78 to 119 days post sowing, C1 and C2, respectively). OM content (g 100g DM) was higher (p ¿ 0.05) for D1 (90.8) Than for D2 and D3 (89.1) and CP content exchange between due dates, (P¿0.05) D3 > D2 > D1 (16.4, 15.3, 13.3 %, respectively) the in vitro production of gas(ml gas g-1 DM)was not different(P¿0.05) between planting dates (185) but for cuts(P¿0.05), being C1 > C2 (199.6 vs 171.7); in vitro degradation of dry matter, there were no differences observed (P¿0.05) between dates (53.11 mg 100 mg of DM) but C1 was superior (P¿0.05) to C2 (59.3 vs 46.9 mg 100 mg of DM).The Protein degradation was estimated by in situ ruminal incubation (RDP, g 100g of DM),being superior (p¿0.05) D2 (71.8) with regards to D1 and D3 (62.9 y 59.3) and C1 > C2 (P¿0.05) (67.6 vs 61.8). Due to the CP content of the Kochia scoparia it is suggested as an alternative source of medium-quality protein to ruminants, having degradation in the rumen of more than 60 %, which is influenced by the maturity of the plant and its date of establishment.